Progressive pension formula and life expectancy heterogeneity - Keivan Diakite; Pierre Devolder (Risks, 2021)
An increasing number of empirical studies have shown a positive relationship between lifetime income and life expectancy at retirement. One's income during the active part of one's career translates into the amount of retirement benefits one might receive, leading to actuarial unfairness inside cohorts of retirees. In order to discuss unfairness and sustainability issues, the Belgium pension reform committee issued a proposal for a point system designed to be both sustainable and adequate. In this paper, we use a similar defined benefit framework in order to set out a compensation mechanism linked to life expectancy heterogeneity during the active part of the career, aiming to reduce unfairness once reaching retirement. This method is based on the progressivity of pension benefit formulae. We implement these ideas in a simple demographic context in order to capture the constraints related to the model.
Keywords: 330; heterogeneity in life expectancy; pension scheme design; progressivity